Airport systems planning, design, and management - De Neufville, Richard 1939-; Odoni, Amedeo R. (New York McGraw-Hill, 2013)
"This is a premier text by leading technical professionals, known worldwide for their expertise in the planning, design, and management of airports"-Provided by publisher.
Includes bibliographical references and index.
Keywords: Airports -- Planning; Airports -- Design and construction; Airports -- Management; Electronic books